REVOLUSI PEMBELAJARAN PAI: OPTIMALISASI TEKNOLOGI DAN MEDIA DALAM MENGHADAPI TANTANGAN PENDIDIKAN MODERN: REVOLUSI PEMBELAJARAN PAI: OPTIMALISASI TEKNOLOGI DAN MEDIA DALAM MENGHADAPI TANTANGAN PENDIDIKAN MODERN - Asip Ependi; Meriyati; Hamidah; Dwi Suci Rahma Putri; Fifi Risana; Agus Jatmiko; Chairul Amriya (LP2M IAIN Sultan Amai Gorontalo, 2025)
Technology and digital media have transformed the world of education, including PAI learning. The purpose of this research is to examine how the utilization of technology and media in PAI learning in the modern era. This research conducted a literature review using a descriptive qualitative approach. The research shows that although technology and media can enhance the quality of learning, they can also present problems such as a shortage of educators and infrastructure imbalances. The use of technology in Islamic Education (PAI) can be an innovative way to improve the quality of Islamic education by optimizing the right strategies.